Aplicação de produtos fitossanitários na cultura dos citros utilizando pulverizador envolvente - Carvalho, Giorge França Gomes de [UNESP] (2014)
The productive sector of the Brazilian citrus industry, the largest at the world in oranges and concentrated citrus juice, faces intense occurrence of pests and diseases. In an attempt to maintain its productivity it makes intense use of pesticides on orchards areas. Place to occurrence, degree of infestation and pest movement have a great influence to crop protection, which the efficiency depends on of distribution of pesticides around canopy. There are many causes that lead to failure of the treatment plant in citrus. Among the main of that the equipment poorly calibrated and rated in terms of size of citrus trees, associated with the project from the sprayers that provide difficulties to better direct sprays to plants. In addition, there are also economic and environmental consequences related to losses by runoff and drift of spraying applied, and sometimes we lose more than 50% of the volume applied. Due that, we elaborate this study to evaluate a surrounding sprayer developed in bases of application rate, spraying distribution and control of Brevipalpus phoenicis (Geijskes, 1939) and fungus Guignardia citricarpa Kiely [Phyllosticta citricarpa (McAlp.) van der Aa .]) at different positions of citrus trees, chosen to constituted greater crop protection problems and to be among the main components in current production costs of citrus in São Paulo. To evaluations will be used two models of tractor-sprayer, a model Arbus 2000® manufactured by Máquinas Agrícolas Jacto S.A., commonly used in citrus in Brazil, considered in this project as the default system (control applied), and another of model Topspray®, manufactured by Herbicat Ltda. equipment, recently launched and developed in a joint with the company and researchers including the authors of this project. The surrounding sprayer brought with it enough characteristics to be considered a viable alternative to use